2015
DOI: 10.1007/s00774-015-0654-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone-adiposity cross-talk: implications for pediatric obesity

Abstract: The rising prevalence of overweight and obesity among pediatric populations has become a major global concern. The objective of this review is to demonstrate potential interactions between the products released by fat tissue and the hormonal production of bone tissue in obese children and adolescents. Advancing the understanding of the complex interactions between adipocyte and osteocyte activities may contribute to the mechanistic understanding of the body's responses to weight loss during adolescence. This k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
(111 reference statements)
2
6
0
Order By: Relevance
“…52 However, increasing evidence has shown that obesity could be a risk factor for osteoporosis. 52,53 Here, we showed a significant bone loss in HFD-induced obesity mice ( Figure 5), in line with reports that obesity is associated with bone loss. 52 We also discovered an inverse correlation between Lox and bone markers in both NCD and HFD mice ( Figure 5).…”
Section: Discussionsupporting
confidence: 91%
“…52 However, increasing evidence has shown that obesity could be a risk factor for osteoporosis. 52,53 Here, we showed a significant bone loss in HFD-induced obesity mice ( Figure 5), in line with reports that obesity is associated with bone loss. 52 We also discovered an inverse correlation between Lox and bone markers in both NCD and HFD mice ( Figure 5).…”
Section: Discussionsupporting
confidence: 91%
“…Fat tissue is an active endocrine organ secreting a host of molecules called adipokines, such as leptin. We have demonstrated the likelihood of bone-adiposity cross-talk in a recent literature review [ 46 ]. We were unable to report that insulin, pro-inflammatory cytokines, adiponectin, PAI-1, nor even bone metabolism markers were predictor variables of weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of paediatric overweight and obesity remains alarming worldwide (15) , accompanied by early metabolic (24) , sleep (25,26) and functional (27) impairments, amongst others, calling for effective preventive and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%